Willingness to Share Knowledge Compared with Selected Social Psychology Theories - Ewa Krok (Contemporary Economics, 2013)
Knowledge is one of the key determinants in the growth and competitiveness of modern enterprises. Hence, it is essential to analyse the factors that induce employees to exchange knowledge. The problem of sharing an intangible asset - in this case, the knowledge of individuals - can be viewed from many perspectives: psychological, economic, organisational, sociological and technological. The aim of this article is to explore selected social psychology theories and to analyse the incentives for people to share knowledge. The article attempts to interpret the willingness to share knowledge through the Social Exchange Theory, the Social Impact Theory, the Theory of Reasoned Action and the Theory of Planned Behaviour. This analysis leads to the following conclusions: we share our knowledge and expect a return; we share our knowledge when we believe that the benefits of this action outweigh the costs; we are pushed to share knowledge by the power of empathy; workers' willingness to share knowledge is influenced by three social processes: subordination, identification and internalisation; the decision to share knowledge is preceded by an intention formed under the influence of an individual attitude towards that behaviour, subjective norms and perceived behavioural control; and the decision to share knowledge is also influenced by additional components, including the knowledge and skills to implement this behaviour, environmental limitations, behavioural emphasis and habits.
Keywords: A12; M50; 330; knowledge sharing; willingness to share knowledge; social psychology theories; individual competencies; direct sales; multilevel marketing; discriminant analysis; correlation analysis